Trading Blocs and Welfare : How Trading Bloc Members Are Affected by New Entrants - Hacker, R.; Hussain, Qaizar (Washington, D.C. : International Monetary Fund, 1998)
This paper uses the three-country duopoly model to examine the effects of lowered trade barriers when a new entrant joins a trading bloc. There are two firms-a small-country firm and a large-country firm within the bloc-and three markets-two within and one (new entrant's) outside the bloc. The analysis generally shows greater gains for the small-country than for the large-country firm. The small-country firm will export more to the external country than the large-country firm. But if tariffs decline, the export share of the large-country firm will increase relative to the small-country firm's, though profits will improve more for the latter.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet